Influence of working memory on patterns of motor related cortico-cortical coupling. - Serrien, D; Pogosyan, A; Brown, P (2004)
Working memory is implicated in various higher-order cognitive operations. We hypothesized that the availability of a temporal representation in working memory would limit the extent of cortico-cortical coupling necessary to undertake a self-paced rhythmic movement. To this end we examined modulations in cortico-cortical interactions as determined by EEG coherence during a delay interval and subsequent movement reproduction. Right hand movement was initially paced by a metronome beat every 0.9 s, followed by a delay interval, after which hand movement was repeated in an unpaced manner. Movement reproduction after a long (22.5 s, corresponding to 25 movement cycles) compared to a short (5.4 s, corresponding to 6 movement cycles) delay interval was associated with an increased degree of functional coupling in the beta frequency band (12-30 Hz) of the left (movement-driving) hemisphere (F3-FC3, F3-C3 and F3-P3 connections) as well as mesial regions (FCz-FC3, FCz-C3 and Cz-FC3 connections) even though overall behavioral characteristics were not influenced. In addition, analysis of the EEG coherence in the delay period revealed a bilateral frontal network (F3-F4, F3-FC4, F4-FC3 and FC3-FC4 connections). Activity in the latter tended to be synchronized in the theta band (4-8 Hz) and was significantly less strong at 22.5 s than 5.4 s. These data suggest that working memory may be partly subserved by synchronization in a bilateral frontal network and may provide an intrinsic contextual influence that shapes the pattern of cortico-cortical interaction during a given task.